Direct‐Acting Antiviral Treatment Use Remains Low Among Florida Medicaid Beneficiaries With Chronic Hepatitis C - Haesuk Park; Hyun Jin Song; Xinyi Jiang; Linda Henry; Robert L. Cook; David R. Nelson (Hepatology Communications, 2021)
Medicaid prior authorization (PA) policies for treatment of hepatitis C virus (HCV) with direct‐acting antiviral (DAA) therapy are changing. We aimed to evaluate effects of changes in PA requirements on treatment uptake and to determine the factors associated with DAA treatment among Florida Medicaid beneficiaries with HCV. This is a retrospective cohort analysis of Florida’s Medicaid administrative claims and electronic medical records (2013‐2018). A total of 14,063 newly diagnosed patients with HCV were grouped based on human immunodeficiency virus (HIV) co‐infection and/or a substance use disorder (SUD) (7,735 HCV mono‐infected with a SUD, 5,180 HCV mono‐infected without a SUD, 564 HCV/HIV co‐infected with a SUD, and 584 HCV/HIV co‐infected without a SUD). Although the treatment rate increased three‐fold after June 1, 2016, when a fibrosis‐stage restriction was eliminated, only 8% received DAAs. Compared to HCV mono‐infected without a SUD, HCV mono‐infected with a SUD and HCV/HIV co‐infected with a SUD were 47% (adjusted hazard ratio, 0.53; 95% confidence interval, 0.47‐0.60) and 59% (adjusted hazard ratio, 0.41; 95% confidence interval, 0.28‐0.61) less likely to initiate DAAs. Those with HCV/HIV/SUD did not experience a DAA initiation increase after a fibrosis‐stage restriction was eliminated. Compared with Whites, Blacks were less likely to receive DAAs but were more likely to complete treatment. Use of medication‐assisted therapy was low, despite those on medication‐assisted therapy being 60% more likely to initiate DAA therapy and no more likely to discontinue therapy. Conclusion: Despite changes in Florida’s Medicaid PA requirements for DAA treatment, only 8% received treatment. Disparities in treatment access were found among patients with HIV and a SUD, and who were Black.